Performance Optimization - Lufthi Al Riza Siregar, Ahmad; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
Companies really need competent and quality human resources, especially in this era of globalization. All business organizations must be ready to adapt and strengthen themselves in order to compete so that they are able to answer all challenges in the future. Human resources in this case are employees who always play an active and dominant role in every organizational activity because humans are planners, actors and determinants of the realization of goals. This research aims to examine the influence of rewards and competencies on employee performance with punishment as an intervening variable at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Competency has a positive and insignificant effect on employee performance with an original sample value of 0.127 and ap value of 0.210. Competence has a positive and significant effect on Punishment with an original sample value of 0.433 and ap value of 0.000. Punishment has a positive and significant effect on employee performance with an original sample value of 0.601 and ap value of 0.002. Rewards have a positive and insignificant effect on employee performance with an original sample value of 0.158 and ap value of 0.216. Rewards have a positive and significant effect on Punishment with an original sample value of 0.541 and ap value of 0.000. Competence has a positive and significant effect on employee performance through punishment with an original sample value of 0.260 and ap value of 0.006. Rewards have a positive and significant effect on employee performance through punishment with an original sample value of 0.325 and ap value of 0.006.